Costa Rica : Selected Issues and Analytical Notes. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper examines several real sector issues, including estimates of potential output, the effect of Intel's withdrawal on gross domestic product (GDP), labor market and inequality and electricity prices in Costa Rica. The production function approach shows that the main drivers of fluctuations in GDP growth are total factor productivity (TFP) and labor supply. These results on TFP, however, should be interpreted with caution. The TFP measure is a residual-the difference between output growth and the growth in the quantity (and quality) of inputs. Estimates suggest that potential GDP growth is about 4.3 percent, the output gap is broadly closed, and Intel's withdrawal will lower real GDP growth in about 1/2 percentage point. Significant wage premia are identified across public versus private sectors and some evidence of intergenerational inequality is also presented. Electricity tariffs are found to be regionally competitive albeit with inefficiencies in their determination.